New approaches for estimating risk from exposure to diethylstilbestrol. - Cunha, G R (1999)
A subgroup from a National Institute of Environmental Health Sciences, workshop concerned with characterizing the effects of endocrine disruptors on human health at environmental exposure levels considered the question, If diethylstilbestrol (DES) were introduced into the market for human use today and likely to result in low-dose exposure of the human fetus, what would be required to assess risk? On the basis of an analysis of the quality of data on human DES exposure, the critical times and doses for inducing genital tract malformations and cancer must be determined. This would be facilitated through analysis of the ontogeny of estrogen receptor expression in the developing human genital tract. Models of low-dose estrogenic effects will have to be developed for human and rodent genital tract development. Mouse models offer many advantages over other potential animal models because of the wealth of the earlier literature, the availability of sensitive end points, the availability of mutant lines, and the possibility of generating genetically engineered model systems. Through multidisciplinary approaches, it should be possible to elucidate the cellular and molecular mechanisms of endocrine disruption elicited by estrogens during development and facilitate an assessment of risk to humans.